2012
DOI: 10.4209/aaqr.2012.05.0132
|View full text |Cite
|
Sign up to set email alerts
|

A Review of CO2 Capture by Absorption and Adsorption

Abstract: Global warming resulting from the emission of greenhouse gases, especially CO 2 , has become a widespread concern in the recent years. Though various CO 2 capture technologies have been proposed, chemical absorption and adsorption are currently believed to be the most suitable ones for post-combustion power plants. The operation of the chemical absorption process is reviewed in this work, together with the use of absorbents, such as the ionic liquid, alkanolamines and their blended aqueous solutions. The major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
921
0
19

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,458 publications
(942 citation statements)
references
References 203 publications
(189 reference statements)
2
921
0
19
Order By: Relevance
“…Thus, the kinetics of adsorption and desorption controls the cycle time and the amount of adsorbent required in the adsorption system. The faster an adsorbent can adsorb/desorbed CO 2 , the less amount of adsorbent will be needed to capture a given volume of CO 2 (Samanta et al 2011;Yu et al 2012). It has been reported that the overall kinetics of CO 2 adsorption is influenced by functional groups present, as well as the pore size and distribution in the support.…”
Section: Adsorptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the kinetics of adsorption and desorption controls the cycle time and the amount of adsorbent required in the adsorption system. The faster an adsorbent can adsorb/desorbed CO 2 , the less amount of adsorbent will be needed to capture a given volume of CO 2 (Samanta et al 2011;Yu et al 2012). It has been reported that the overall kinetics of CO 2 adsorption is influenced by functional groups present, as well as the pore size and distribution in the support.…”
Section: Adsorptionmentioning
confidence: 99%
“…If an appropriate sorbent and proper operation conditions are chosen, continuous removal of CO 2 up to 80 % can be achieved with ease under favorable economics Park et al 2006a, b). Various metal oxides such as Na-, K-and Libased materials are considered to be efficient for the CO 2 adsorption operation, but the seriousness of diffusion resistance has hindered their commercial consumption (Iwan et al 2009;Yu et al 2012). The attrition or abrasion resistance affects the CO 2 capture.…”
Section: Dry Alkali Metal-based Sorbentsmentioning
confidence: 99%
See 2 more Smart Citations
“…[28] A comparison of CO 2 absorption performance of PEI-GO and three different kinds of PEI-impregnated mesoporous silica substrates [29] is given in Table 3. The absorption capacity of PEI-GO is comparable to that of KIT-6-PEI at 25 C. …”
Section: Pei-gomentioning
confidence: 99%